Google Bard: Utility in Drug Interactions - Jacob, Jerry (Scripta Medica, 2023)
Emergency medicine is a busy department with a huge flow of patients with multiple complaints. The department caters to a large cohort of patients simultaneously as well as administers many drugs. This can lead to potential drug interactions. With the advent of artificial intelligence (AI) and language learning model (LLM) we can use these AI enabled programs to help us be cautious yet judicious in our drug delivery and also be a careful vigilante to prevent drug interactions in these patients.